How to Undo Things and Selves with Words: Understanding Literature as Praxis in Virginia Woolf’s Essays on Actresses - Caroline Marie (Sillages Critiques)
Virginia Woolf reflects on her own medium in relation to the notion of personality. This article reads her essay “Personalities” (1947), in which she explores the reader’s response to the personalities of writers, in light of three essays that discuss the art of acting embodied by three celebrated nineteenth-century actresses, “The Memoirs of Sarah Bernhardt” (1908), “Rachel” (1911) and “Ellen Terry” (1941). It argues that Woolf theatricalises literature to understand it through the art of acting, in particular the building up of characters. Actresses embodying nineteenth-century acting, Ellen Terry, Sarah Bernhard and Rachel, as well as Woolf’s contemporary Lydia Lopokova, whose performance is reviewed in “Twelfth Night at the Old Vic” (1933), mediate Woolf’s reflection on literature from different perspectives: writing with the body, reading with gestures, creating from anecdotes, and becoming other.